Kommunizm – eto yest' Sovetskaya vlast' plyus elektrifikatsiya vsey strany
Illustration of Lenin waving Pravda beneath map of Soviet Russia glittering with stars Original title: Коммунизм - это есть Советская власть плюс электрификация всей страны PO-0769